TITLE: INFLUENCE OF SOIL COMPACTION ON ENERGY EFFICIENCY DURING TILLAGE OPERATIONS - Aziza Tajimuratova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Soil compaction is a significant factor influencing the energy efficiency of tillage operations in agriculture. The present review is concerned with an examination of the extant literature on the manner in which compaction increases energy requirements during tillage, and the concomitant implications of this phenomenon in regard to the economic and environmental impact of farming. The article explores the mechanisms through which soil compaction affects energy usage, the long-term consequences of increased tillage depth, and potential mitigation strategies. The review concludes by exploring sustainable farming practices, including reduced tillage, precision farming, and subsoiling, as potential solutions to enhance energy efficiency in the context of soil compaction.